A Continuous Sliding Mode Current Control Based on the Sensitivity Theory for PMSM Drives - Elia Brescia; Massimo Tipaldi; Francesco Torelli; Paolo Roberto Massenio; Luigi Pio Savastio; Giuseppe Leonardo Cascella; Enrico De Tuglie (IEEE Open Journal of Industry Applications)
Sliding mode controllers (SMCs) are commonly used in permanent-magnet synchronous machines (PMSMs) for current control due to their robustness and simplicity. However, high gains used in traditional discontinuous SMC implementations can induce chattering. To address this, disturbance observers are employed to maintain robustness without resorting to high gains. This article introduces a novel continuous asymptotic SMC method for PMSM currents that avoids the need for disturbance observers, resulting in reduced complexity and tuning efforts. The control laws of the two $dq$ -axes currents are obtained through the sensitivity of the tracking errors with respect to the controller outputs. The robustness and convergence properties of the proposed control laws are theoretically studied using the Lyapunov approach. Numerical simulations are used to evaluate the performance and robustness of the proposed controller, followed by experiments to compare it to a discontinuous terminal SMC with and without a disturbance observer. The results clearly demonstrate the superiority of the proposed controller that ensures fast convergence, low chattering, and high robustness to parameter variations without requiring the design of additional disturbance observers.